Seismic Behavior of Tall Rocking Mass Timber Walls - Wichman, Sarah (My University, 2024)
Mass timber buildings are gaining popularity in the United States and around the world as they offer benefits such as fast construction, unique architectural features, and the use of a sustainable building material. Post-tensioned mass timber rocking wall lateral force-resisting systems have made fully mass timber buildings feasible for high seismic areas. The inherent re-centering behavior of these systems provides an opportunity to design for enhanced seismic objectives, creating a resilient system that exceeds code-minimum performance. Despite these advantages, post-tensioned mass timber rocking wall lateral systems are still relatively new and are thus not currently recognized by United States design codes. While using mass timber post-tensioned rocking wall systems for buildings in the 2-5 story range is gaining popularity in research and in building projects around the world, little research has been completed for these systems in the 6-20 story range. To demonstrate the resilient capabilities and validate the use of code alternative design procedures for these systems, an integrated experimental and numerical research program was conducted as part of the large, multi-institutional NHERI TallWood Project. The research presented here is a portion of the larger project. First a post-tensioned rocking wall lateral system was designed for a two-story mass timber building that was tested dynamically at full-scale and results were used to validate the proposed numerical modeling methodology. Next, a performance-based design process, including methods for preliminary design and detailed evaluation with nonlinear response history analysis, was used to design the lateral system for a full-scale 10-story mass timber building. More stringent criteria for interstory drift requirements as well as deformation and force-controlled elements were enforced to target essentially elastic performance under Risk-Targeted Maximum Considered Earthquake MCER demands. To evaluate the design procedure and numerical modeling methodologies, the building was tested under repeated three-dimensional earthquake records that range from those representing a 43-year return period hazard to those representing MCER. This is the tallest building ever tested on a shake table. The outcomes and lessons learned from these tests were used to define a parametric study to investigate wall moment amplification from higher mode effects and make design procedure recommendations for future adoption of this system into building codes. The results of the presented work will help structural engineering practitioners effectively design rocking mass timber wall systems for tall mass timber buildings, provide important experimental and numerical simulation data for eventual inclusion of the system in building codes, and advance the state-of-the-art in earthquake engineering research for mass timber structures.
Thesis (Ph.D.)--University of Washington, 2023
Keywords: Mass Timber; Numerical Modeling; Resilient; Seismic Performance; Shake Table Test; Shear Walls; Civil engineering; Civil engineering